2003
DOI: 10.1007/bf02867380
|View full text |Cite
|
Sign up to set email alerts
|

Studies on biochemical changes with special reference to oxidant and antioxidants in malaria patients

Abstract: Oxidative stress plays an important role in the development of maladal anemia. The present study was undertaken to study the role of oxidant and antioxidants in the patients of Plasmodium falciparum malada (n = 25), Plasmodium vivax malada (n = 25) as against the normal control subjects (n =25). The parameters included are the hematological [hemoglobin, erythrocyte adenosine deaminase (ADA) activity, ADP -induced platelet aggregation] and serum total lipid peroxide as an index of oxidative stress and antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 18 publications
(16 reference statements)
7
39
0
3
Order By: Relevance
“…The presence of IRBCs frequently induces the infiltration of inflammatory-type cells into the placenta, where they cause pathological alterations (26). It has been also shown that P. falciparum trophozoite infected human red cells produce H 2 O 2 and OH ¯ radical about twice as much as normal erythrocytes (17,27). Excess H 2 O 2 could also result in breakdown of heme and release of free iron ions, which in turn form OH¯ through Fenton reaction (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of IRBCs frequently induces the infiltration of inflammatory-type cells into the placenta, where they cause pathological alterations (26). It has been also shown that P. falciparum trophozoite infected human red cells produce H 2 O 2 and OH ¯ radical about twice as much as normal erythrocytes (17,27). Excess H 2 O 2 could also result in breakdown of heme and release of free iron ions, which in turn form OH¯ through Fenton reaction (28).…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, 5-10% of pregnant women may develop severe anaemia (defined as haemoglobin < 70g/l or < 80g/l) (14,15). One of the major reasons for development of malarial anemia seems to be oxidative stress (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of free radicals through oxidative stress in the physiopathogenesis of malaria has been documented. 16,32,33 Malaria parasites release free radicals causing oxidative stress during the part of their life cycle when they inhabit erythrocytes. As the infection progresses, they also activate macrophages, one consequence of which is extracellular release of reactive oxygen species (ROS), with the propensity of inducing oxidative damage and cell destruction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, vitamin E is transported by selenoproteins (Alfin-Slater and Morris, 1963). Thus, these antioxidant species in the extracts may play an important role in scavenging the ROS produced during Plasmodium species infection either independently or synergistically through mechanisms which may include interference with lipid peroxidation, which has been shown to occur in malaria (Kulkarni et al, 2003) and termination of free radical chain reactions (Sardesai, 1995). Furthermore, the higher activities obtained for the methanolic extract may result from the higher concentrations of these antioxidant species in this extract compared to other extracts.…”
Section: Discussionmentioning
confidence: 95%